Aid and environment in Africa: The case of Tanzania - Godius Kahyarara (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
This paper provides an assessment of what aid has actually been doing in the area of environment in Tanzania through a critical review of the flows, modalities and management of aid. Focusing on the funding for environmental degradation projects, the study notes that budget expenditure allocation to these activities is around 0.04 per cent of Tanzania's total expenditure. This is a problem given that in the near future financing for climate change alone would need around US1 billion per year (or nearly 10 per cent of the budget). Ultimately, aid money is critical for Tanzania, as over 90 per cent of funds for environment come from donors. To ensure maximum effectiveness of aid, Tanzania, in collaboration with its many development partners, introduced the Tanzania Joint Assistance Strategy. This resulted in an improvement in the country's operational development strategies and by 2010 out of 13 indicators with applicable targets, six were met. The paper concludes that environmental efforts in Tanzania depend heavily on donor money. This will not be sustainable because, with time, moral hazard will develop to the extent that environmental protection obligations will need to be integrated with economic activities. This calls for reinforcing the 'polluter pays' principle.
Keywords: F30; F30; O19; 330; aid; development; environment